Analisis Pengaruh Brand Image dan Brand Awareness terhadap Keputusan Mengadakan Kegiatan MICE di The Westin Resort Nusa Dua Bali - Kelvin; Sarudin, Rendy (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2024)
The Westin Resort Nusa Dua Bali is a convention hotel managed by Marriott International under the premium brand category, featuring the renowned Bali International Convention Center (BICC). This study investigates the influence of Brand Image and Brand Awareness variables on the Decision to Hold MICE Activities at The Westin Resort Nusa Dua Bali. The research employs a quantitative method, utilizing primary and secondary data sources, conducting validity tests, descriptive statistical mean tests, classic assumption tests, multiple linear regression analysis, hypothesis testing through T-tests, F-tests, and coefficient of determination tests processed using SPSS software. The sample consists of 77 respondents who have held MICE activities at The Westin Resort Nusa Dua Bali during the Q1-Q2 period of 2023. The results reveal that the overall mean value of variable X1 (Brand Image) is 4.43, variable X2 (Brand Awareness) is 4.48, and the overall mean value of variable Y (Decision to Hold MICE Activities) is 4.46. The Ttest and Ftest results show significance values <0.05, with Tvalue > Ttable and Fvalue > Ftable indicating that brand image and awareness variables have partial and simultaneous effects on the Decision to Hold MICE Activities. The Coefficient of Determination (R2) test yields an adjusted R2 value of 0.300, suggesting that 30% of the variability in variable Y can be explained by variables X1 and X2.